Dietary black cumin (Nizella sativa) seed meal on growth and meat yield performance of broilers (SAARC Journal of Agriculture, 2016)
A total of 144, day old as hatched Cobb-500 broilers were fed adlibitum basis on a diet with 0%, 0.5%, 1.0% and 1.5% of Black Cumin Seed Meal up to 35 days of age to compare the effect of BCSM as herbal growth promoters on growth performance, meat yield characteristics and profitability of broilers. The experimental diets consisted of broiler starter and broiler grower, which were fed from 0-16 and 17-35 days of age, respectively. Diets supplemented with 1.5% BCSM showed significant effect on live weight at 21, 28 and 35 days of old in broilers in various groups as compared to that of control group. Better feed conversion (2.02) also noticed at 1.5% level of BCSM at early stage (14 days of old) of broilers. There was no significant difference (P>0.05) among the average live weight, dressing yield, thigh meat, wing meat, heart, gizzard liver, at 0%, 0.5%, 1.0% and 1.5% level of BCSM diet. But difference found within breast meat, drumstick meat, abdominal fat and skin of broilers at 1.5% level of BCSM diet. It may be concluded that supplementation of BCSM at 1.5% had the highest significant effect (P